Collaborative Care at a Distance: Student Therapists' Experiences of Learning and Delivering Relationally Focused Telemental Health. (11th April 2020) - Springer, Paul; Bischoff, Richard J.; Kohel, Kara; Taylor, Nathan C.; Farero, Adam
Abstract : There is mounting evidence that telemental health is an effective delivery method for treating a variety of mental, emotional, behavioral, and relational health problems. While many of the therapeutic skills leading to the effectiveness of face‐to‐face treatments are transferable, the effectiveness of telemental health requires unique skills. The purpose of this phenomenological study was to determine the experience of learning how to use videoconferencing to deliver relationally focused mental health care. Participants included 10 graduates of a COAMFTE‐accredited master's degree program emphasizing training in telemental health. Each student had practicum placements that required videoconferencing to deliver relationally based psychotherapy. Analysis of interview data revealed (a) personal reservations about distance delivery; (b) the importance of scaffolding student learning through curriculum, supervision, and mental health‐care delivery protocols; (c) the technological barriers associated with this delivery method; and (d) overcoming technological barriers through intentionality.